Pengenalan Pembuatan Telur Bacem Dekoratif Malangan dengan Pewarna Alam Kayu Secang dan Teh Hijau - Setianingsih, Tutik; Danar Purwonugroho; Yuniar Ponco Prananto; Afif Eka Rahma Setiyanto; Adi Kurnia Soesantyo; Silvi Zakiyatul Ilmiyah; Kashifa Maria Jihan (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
Activity of DPP-SPP 2022 community service was conducted with workshop method. Purpose of activity is to improve quality of Malang cullinary, especially chicken egg, to get more nutrious and healthy one using natural dyes such as green tea andsappan wood. The steps to make the decorative bacem egg included the boiling of eggs, decorative peeling of eggs, boiling of mixture (dyes, the decorative eggs, and spices), immersion, and peeling of the decorative bacem eggs. The workshop was performed with getting arround method and online counselling through youtube. Number of participants is 19 people. In the method, the participants take the book module and product examples. They filled evaluation form after tasting some products. In online workshop, counseling of the decorative bacem egg cooking was presented by the students. In other side, informations about nutritions, antioxidant substances, and health research about tea and sappan wood were given by the lecturers. Based on the evaluation, the most participants gave score of good for method, more decilious taste and interesting appearance for the decorative bacem eggs using sappan wood than tea, and planning of the technology application was mostly for bussiness.